Arctic Service Test of Laser Rangefinder AN/GVS-3 under Arctic Winter Conditions. - Rucks, Michael G. (1970)
An Arctic Service test was conducted on the Laser Rangefinder, AN/GVS-3, by the U. S. Army Arctic Test Center at Fort Greely, Alaska, from 3 March 1970 to 9 March 1970. One laser operator and a test officer operated, recorded, and analyzed performance characteristics, arctic mounting, rangefinding capability, durability, reaction time, human factors, maintainability and safety of the AN/GVS-3 laser operations under arctic winter conditions at temperatures ranging to -12 F. Equipment was cold-soaked prior to all testing. Testing was conducted at a USATECOM approved range in accordance with USAATC Regulation STEAC-AT-385-1.